2018
DOI: 10.1128/aem.02306-17
|View full text |Cite
|
Sign up to set email alerts
|

An Archaeal Fluoride-Responsive Riboswitch Provides an Inducible Expression System for Hyperthermophiles

Abstract: Robust genetic systems for the hyperthermophilic have facilitated the overexpression of native genes, enabled the addition of sequences encoding secretion signals, epitope, and affinity tags to coding regions, and aided the introduction of sequences encoding new proteins in these fast-growing fermentative heterotrophs. However, tightly controlled and easily manipulated systems facilitating regulated gene expression are limited for these hosts. Here, we describe an alternative method for regulatory control reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…The sugar-inducible system provides a variety of choices for the use of multiple sugars but may interfere with the central metabolism of the organism of interest, which must be taken into consideration. Recently, an archaeal fluoride-responsive riboswitch composed of the Tk-FRR cassette was also constructed as an inducible expression system for hyperthermophiles (31). In our study, we identified an HHP-inducible promoter (P hhp ) in P. yayanosii.…”
Section: Discussionmentioning
confidence: 86%
“…The sugar-inducible system provides a variety of choices for the use of multiple sugars but may interfere with the central metabolism of the organism of interest, which must be taken into consideration. Recently, an archaeal fluoride-responsive riboswitch composed of the Tk-FRR cassette was also constructed as an inducible expression system for hyperthermophiles (31). In our study, we identified an HHP-inducible promoter (P hhp ) in P. yayanosii.…”
Section: Discussionmentioning
confidence: 86%
“…Given our desire to directly demonstrate that reduced FttA activity impacts termination in vivo , coupled with our inability to generate T. kodakarensis strains encoding enzymatically-impaired FttA variants, we next reduced FttA activity by limiting FttA expression and altering steady-state FttA WT protein levels. To ensure that introduced and regulated expression of TK1428 did not impact TK1429 expression 46 , we separated TK1428 expression from TK1429 by introduction of a new promoter and intrinsic termination sequence, then placed the TK1428 coding sequences downstream of sequences encoding an archaeal fluoride-responsive riboswitch 47 , thereby generating strain IR5 ( Figure 4g ). Construction of IR5 was only possible when cultures were continuously provided with fluoride even though fluoride impairs growth of T. kodakarensis 47 , supporting that very limited expression of TK1428 was not compatible with life.…”
mentioning
confidence: 99%
“…To ensure that introduced and regulated expression of TK1428 did not impact TK1429 expression 46 , we separated TK1428 expression from TK1429 by introduction of a new promoter and intrinsic termination sequence, then placed the TK1428 coding sequences downstream of sequences encoding an archaeal fluoride-responsive riboswitch 47 , thereby generating strain IR5 ( Figure 4g ). Construction of IR5 was only possible when cultures were continuously provided with fluoride even though fluoride impairs growth of T. kodakarensis 47 , supporting that very limited expression of TK1428 was not compatible with life. Steady-state FttA levels in IR5 strains grown in the absence and presence of fluoride reveals a modest ~2-fold change in FttA levels in vivo when fluoride is removed from cultures ( Figure 4h and Supplementary Information Figure 2 ), yet even this modest alteration significantly and reproducibly impacts transcription termination in vivo ( Figure 4d - f ).…”
mentioning
confidence: 99%
“…A cross all three domains of life, evolution has generated a diverse set of functional RNAs known to play important roles in cellular homeostasis and gene regulation [1][2][3][4][5][6] . These biopolymers fold into modular, three-dimensional structures capable of binding specific ligands (aptamers) or catalyzing specific biochemical reactions (ribozymes).…”
mentioning
confidence: 99%